PERUBAHAN PENGGUNAAN LAHAN PADA LANSKAP SAWAH TERAS DAN FAKTOR PENYEBABNYA DI HOKUDAN CHO, HYOGO PREFECTURE, JEPANG - Rai Asmiwyati, I G.A.A.; Hadi Susilo Arifin, Nurhayati (Bumi Lestari; Vol 7 No 1, 2012)
The research were identified terraced land use change and its causality as well as analyzed the relationship with irrigation management systems in a terraced paddy landscape in Hokudan-Cho, Awaji Island, Hyogo Prefecture, Central Japan. Between 1963 and 2000. As the result, the land use change from 1963 to 2000 was dominated by the decrease of terraced paddy field into other utilizations. It became clear that the social factors which cannot be seen directly in the field induced influences on the pattern of landscape change and the land management in the two types of irrigation system. Customary social rules which is contained in Tazu system were strongly contributed to the sustainability of the terraced paddy fields. Hoping this research also can be an inspiration to conserve the landscape of terraced paddy field in Bali Island.
Keywords: rice terraced irrigation, land use change, rice terraced landscape